The digital watermarking algorithm using discrete chaotic maps - Sidorenko, A. V.; Shakinko, I. V. (Sistemnyĭ analiz i prikladnai͡a︡ informatika., 2020)
The algorithm of formation, embedding and extracting of digital watermarks using discrete chaotic maps is considered. The key feature of the developed algorithm is the formation of the watermark using the discrete chaotic map and the restoration of this watermark after the image transmission via the communication channel. This is possible through the use of the developed method that searches for initial values of discrete chaotic map variables used in the formation of the watermark. The algorithm testing re sults are given. It is established that the proposed algorithm is able to identify the modified image areas. The algorithm is resistant to image conversion in JPEG format and to distortion up to 14 % of the image pixel values due to the presence of noise. Thus, the proposed algorithm can be used to solve real problems of the defense of digital images transmitted by communication channels.